Java EE 6 cookbook for securing, tuning, and extending enterprise applications : packed with comprehensive recipes to secure, tune, and extend your Java EE applications - Knutson, Mick (Packt Pub., 2012)
Packed with comprehensive recipes to secure, tune, and extend your Java EE applications with this book and ebook.